El anime como herramienta de comunicación, integración y forjadora de identidades en la subcultura Otaku de los adolescentes del club Ichiban de la ciudad de Quito - Falconí Benavides, Cristian Daniel (2014)
This paper addresses the perspective of anime as a tool to communicate, integrate and forge identities within the Otaku subculture. This study is done from the Symbolic Interaction and Social Constructivism, taking communication as a process of interaction between individuals where shared symbolic representations arising from the importance their cultural context